PILKADA DARI PERSPEKTIF INCUMBENT (Studi Analisis Pilkada Kabupaten Batang Periode 2017-2022) - Teguh Adi Prasojo Teguh Adi Prasojo (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Implementation of direct local elections intended to further democratize the local elections. The purpose either contained in the implementation of the elections was still far short of expectations since the fact of elections is still in need of improvement in many aspects one of which was the election as a means to legitimize the local authority to make the local elections as a means to legalize their power, and they can both with easy to carry out political dynasty against their close relatives. All these shortcomings urgent we to complete because any shortcomings that still exist precisely then result in the emergence of the reluctance of the people who actually have great potential as occurs in Yoyo Riyo Sudibyo are reluctant to re-nominate themselves as regents, citing fears of